Cutaneous and Laryngeal Squamous Cell Carcinoma in Mixed Epidermolysis Bullosa, Kindler Syndrome - Hiromi Mizutani; Koji Masuda; Naomi Nakamura; Hideya Takenaka; Daisuke Tsuruta; Norito Katoh (Karger Publishers, 2012)
Kindler syndrome is a rare autosomal recessive genodermatosis characterized by trauma-induced acral blisters in infancy and childhood, photosensitivity, and progressive poikiloderma. Other clinical features include chronic erosive gingivitis, dysphagia, esophageal and urethral strictures, ectropion, and an increased risk of mucocutaneous squamous cell carcinoma. We describe a patient with Kindler syndrome associated with squamous cell carcinoma of the skin and larynx. He had squamous cell carcinoma on his left knee with simultaneous unresectable laryngeal carcinoma at the age of 43 years. The squamous cell carcinoma on his knee was excised and the laryngeal carcinoma was treated with radiation therapy. Although pathophysiology of Kindler syndrome and its frequency of association with cancer are still not fully elucidated, we speculate that long-term erosion and regeneration of mucosal and cutaneous surfaces may have induced squamous cell carcinoma on the patient's knee and larynx.